Hybrid models of hydraulic systems for hardware-in-the-loop simulation. Part 2: Experiments - J. A. Ferreira (2004)
The use of new control schemes for hydraulic systems has been the object of study during the last few years. A simulated environment is the cheapest and fastest way of evaluating the relative merits of different control schemes for a given application. Real-time simulation allows parametrization and test of the performance of real controllers. This paper describes the set-up of a real-time simulation platform to perform hardware-in-the-loop simulation experiments with the hydraulic models proposed in the companion paper (Part 1). A set of parametrization techniques are proposed for the semiempirical models of a valve-controlled hydraulic cylinder. Manufacturers data sheets and/or experimental measurements were used to adjust the model parameters. Some of these were directly calculated and others were estimated through the use of optimization techniques. Closed-loop control experiments were then performed on the real-time simulation platform and on the real system, in order to evaluate the real-time performance of the developed models.